Developing Cognitive Ability for Pre-schoolers through Accustomation to Reading Vietnamese - Huong, Nguyen Thu; Hanh, Duong Tuyet; Huong, Le Thi (VNU Journal of Science: Education Research, 2021)
This paper aims to share the benefits of teaching preschool children to read Vietnamese to help shape and develop their ability to read. The benefits shared in this paper can be used as a reference for further study and for parents who want to teach their children Vietnamese literacy.